Effect of litter mixture on litter decomposition and nutrient release of three agroforestry species in Sudano-Guinean savannah of Ngadoundere, Adamawa Cameroon - Massai Tchima Jacob; Babe Ndara Gregoire; Maigari Pale; Djouka Nembot Pélagie; Ibrahima Adamou (Journal of Degraded and Mining Lands Management, 2020)
In order to maintain or improve the soil fertility of agricultural systems in Ngaoundere, an experiment on the decomposition of simple litters and mixtures of Harungana madagascariens, Vitelaria paradoxa and Syzygium guineense var. macrocarpum was conducted in a field using the litterbag method. This experiment was made of single species and their mixtures of which gave three uneven mixtures (5VP, 5HM and 5SM) and one even mixture (3E) amounting to seven treatments (THM, TVP, TSM, 3E, 5HM, 5VP, and 5SM). The experimental design was a completely randomized block with three replications. 126 samples of 10 g each were introduced in a field for 24 weeks and a deduction of 3 samples was made at 2, 4, 6, 10, 16 and 24 weeks. The remaining dry mass, rates of decomposition, half time and the nutrient release in the soil were determined. The results showed that the remaining dry mass varied from 67.95% in TSM (S. guineense) to 22.02% in TVP (V. paradoxa). The rate of decomposition ranged from 0.033 for 5SM (mixture 50% of S. guineense and 25% for each of the two other species) to 0.055 in 3E with respectively 19, 64 to 12, 56 as a half-time. The initial chemical content and that at the end of the experiment of the simple and mixed litters varied significantly within the treatments. The mixture of litter released more nitrogen and carbon than the individual litter and the pattern was ranged as follow 3E>5VP>5HM>5SM>TVP>THM>TSM. The pattern of phosphorus release in the soil was ranged in the following order: TVP>TSM>THM>5VP>3E>5HM>5SM, indicating that the individual litter released more phosphorus on the soil than their mixture. These preliminary results will not only contribute in the comprehension of the decomposition process mechanism of Ngaoundere but also will permit in choosing the type of the litter and mixture with release more nutrient in the soil for improvement of agricultural system fertility.